The Importance of Applying Maqashid al-Sharia in The Islamic Financial System: The Urgency of Maqashid al-Sharia in Islamic Finance - Fanshurna, Toton (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
Maqashid al-sharia is a relevant approach as the basis for developing Islamic financial systems, operations, and products. The maqashid al-sharia holistic order is a light for the development of the Islamic financial system, especially in answering the dynamics of questions based on benefit. The Islamic financial system is part of the prerequisites that must be developed, not only at the conceptual level but also practically. Islam has provided comprehensive textual sources in providing human-first boundaries. But that alone is not enough, if it is not balanced with social inference. Maqashid al-sharia theory in the study of the Islamic financial system is a step forward in developing the most ideal Islamic economic model. This is because maqashid al-sharia can be used as a tool to help solve Islamic economic problems, especially in establishing rules or laws.